Subtractive panning for the isolation of monoclonal PEPITEM peptide antibody by phage display - Mohammed Alassiri; Jing Yi Lai; Angela Chiew Wen Ch’ng; Yee Siew Choong; Asma Alanazi; Theam Soon Lim (Scientific Reports, 2023)
Abstract Antibody phage display is a key tool for the development of monoclonal antibodies against various targets. However, the development of anti-peptide antibodies is a challenging process due to the small size of peptides for binding. This makes anchoring of peptides a preferred approach for panning experiments. A common approach is by using streptavidin as the anchor protein to present biotinylated peptides for panning. Here, we propose the use of recombinant expression of the target peptide and an immunogenic protein as a fusion for panning. The peptide inhibitor of trans-endothelial migration (PEPITEM) peptide sequence was fused to the Mycobacterium tuberculosis (Mtb) α-crystalline (AC) as an anchor protein. The panning process was carried out by subtractive selection of the antibody library against the AC protein first, followed by binding to the library to PEPITEM fused AC (PEPI-AC). A unique monoclonal scFv antibodies with good specificity were identified. In conclusion, the use of an alternative anchor protein to present the peptide sequence coupled with subtractive panning allows for the identification of unique monoclonal antibodies against a peptide target.